Control of Biodegradability of Polyurethane Foam Based on Palm Oil by Ratio of Soft Segment on the Polymer Backbone - Haryono, Agus; Triwulandari, Evi; Sondari, Dewi; Randy, Ahmad; Ridwanuloh, Asep Muhamad (Annales Bogorienses, 2010)
Polyurethane is polymer synthetic which is formed by reaction between polyols and polyisocyanates. Polyols are compounds which contain two or more hydroxyl groups. Polyurethane can be applied in various forms, such as foam, elastomeric, coating and adhesive. In this work, we developed polyurethane foams by using polyols based on palm oil. Palm oil based polyols as soft segments in the polyurethane backbone accelerate biodegradable process of the polyurethane. Biodegradability is the ability of material to be utilized as a carbon source by microorganisms and converted safely into carbon dioxide, biomass and water. Commercially available polyurethane foams are usually produced from petrochemical based polyols that they are not biodegradable. The biodegradability study was conducted by using Aspergillus niger (fungi) and Pseudomonas aeruginosa (bacteria), with variation of method and media for biodegradation. Rigid polyurethane foam was synthesized by using one shoot process method, which is reaction between palm-based polyol mixture and methylene diphenyl diisocyanate (MDI) at room temperature. The effect of variation of ratio of polyisocyanates (NCO) as hard segment and polyols (OH) as soft segment to the properties of polyurethane foams were studied in detail. Study of the effect NCO/OH ratio was conducted with variation ratio of 0.8, 1.0 and 1.2. Increasing hard segment (NCO) ratio to the soft segment (OH) affected in the decreasing of hydrophilicity of foam. Thus, the penetration of water into bulk of polymer decreased. The biodegradability of foam was also affected by the soft segment ratio on the polymer backbone.